Desain dan Kinerja Mesin Terintegrasi untuk Mencacah Daun Sawit dan Mengempa Pelepah Sawit - Ramayanty Bulan; Tineke Mandang; Wawan Hermawan; Desrial Desrial; Agussabti Agussabti (PERTETA, 2018)
AbstractOil Palm frond wastes that are stacked in the rows between oil palm plants take a long time to decompose. To accelerate the decomposition, oil palm leaves need to be chopped into small size and the palm frond need to be compressed into flat. This research aims to design and analyze the performance of an integratedmachine for chopping oil palm leaves and compressing fronds. The design of the machine is performed using engineering characteristics of palm leaves and fronds. The machine consists of palm leaf cutting unit, palm compressing unit and palm leaf chopping unit. All units are integrated and powered by a diesel engine. The leaf cutter used circular blades, the frond compressor used two pairs of grid-rolls and the leaf chopper used a reel-bed knife. All units were tested in order to obtain the machine capacity, percentage of leaves cut, percentage of reduction and increase in frond dimension and chopping leaves size. Leaf cutting unit was tested at blade speeds of 480, 640, and 800 rpm. The compressing unit was tested at rollers speeds of 70, 90, and 110 rpm. The chopping unit was tested at blade speeds of 800, 1200, and 1600 rpm. The test results showed that the optimum machine capacity was 207 frond/h (equal to 1.97 ton/h), leaf cutting was 83.01%, frond height decrease was 18.18 %, fronds width increase was 41.20%, and chopping leaves length and width were 23.3 mm, 3.20 mm, respectively. The optimum operation condition was achieved at cutting blade speed of 640 rpm, 110 rpm compressing rolls speed, and 1600 rpm chopping blade speed.AbstrakLimbah pelepah sawit yang ditumpuk pada alur di antara tanaman kelapa sawit membutuhkan waktu yang lama untuk terdekomposisi. Untuk mempercepat dekomposisi, daun sawit perlu dicacah menjadi ukuran kecil dan pelepah sawitnya perlu dikempa menjadi pipih. Penelitian ini bertujuan mendesain dan menganalisis kinerja mesin pencacah daun dan pengempa pelepah sawit. Desain mesin dilakukan menggunakan data karakteristik teknik dan mekanik dari pelepah sawit. Mesin terdiri dari unit pemotong daun sawit, unit pengempa pelepah sawit dan unit pencacah daun sawit. Unit unit mesin tersebut diintegrasikan dengan penggerak sebuah motor diesel. Pemotong daun menggunakan pisau tipe circular,pengempa pelepah menggunakan dua pasang grid-rolls dan pencacah daun menggunakan pisau reelbedknife. Semua unit diuji kinerjanya untuk memperoleh kapasitas mesin, persentase daun terpotong,persentase pengurangan dan pertambahan dimensi pelepah dan ukuran cacahan daun. Unit pemotong daun diuji pada kecepatan putar pisau 480, 640, dan 800 rpm. Unit pengempa diuji pada kecepatan putarrolls 70, 90, dan 110 rpm. Unit pencacah diuji pada kecepatan putar pisau 800, 1200, dan 1600 rpm. Hasil pengujian menunjukkan bahwa kapasitas oprimum mesin adalah 207 pelepah/jam (setara 1.97 ton/jam), persentase daun terpotong 83.01 %, persentase pengurangan tinggi pelepah 18.18%, persentase pertambahan lebar pelepah 41.20%, panjang cacahan daun 23.3 mm dan lebar cacahan daun 3.20 mm.Kondisi optimum dicapai pada kecepatan putar pisau pemotong daun 640 rpm, kecepatan rolls pengempa 110 rpm dan kecepatan pisau pencacah 1600 rpm.